Food processing enterprises (to be continued) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Promotion des petites entreprises agroalimentaires en Afrique. Échanges de savoir-faire, systèmes d apprentissage et institutions locales (Bénin, Sénégal) By J-J Magloire Bazabana & J Muchnik, CTA, Wageningen, 2001. 140 pp. CTA number 1030. 10 cre